PENEMPATAN PECANDU NARKOTIKA KE DALAM PANTI TERAPI DAN REHABILITASI - MARULI TUA SIREGAR (JURNAL PROINTEGRITA, 2018)
The objective of the research was to find out, to analyze and to understand some factors which caused narcotics abuse, the procedure of placing narcotics addicts in the home for therapy and rehabilitation, and obstacles in placing narcotics addicts in the home for therapy and rehabilitation. The research used library research in collecting the data from various reading materials such as books, magezines, experts' opinions, regulations concerning the factors that enabling the narcotics abuse, and procedure of placing narcotics addicts in the home for therapy and rehabilitation. The field research consisted of direct research in Medan District Court and the other institution concerning child protection by using oral or interview technique. The result of the research shows that the factors which cause the narcotics abuse, according to the narcotics addicts are: to get experience, to flee from reality, to avoid the loneliness and to get emotional experience, to dealt with the emptiness and boredom of hectic life, to avoid disappointment, unrest, and various difficulties which are hard to be solved, to change their personality, to boost the sexual desire, and to search for the meaning of life. The procedure of placing narcotics addicts in the home for therapy and rehabilitation is accordance with the Article 54 and Article 103 of Law No. 35/2009 on Narcotics in which the judge can hand down the verdict as follows: The judge may order the defendant to have the treatment and/or nursing care when the narcotics addict is not proved guilty of committing narcotics criminal act. In deciding the duration of rehabilitation, the judge should consider the level of addiction of the defendant so that it needs explanation from experts as the standard in the process of therapy and rehabilitation. The obstacles in the implementation of therapy and rehabilitation for narcotics addicts are negative impact and the effect of globalization, especially in the advancement of transportation and communication technology. Moreover, drug dealers organize internationally and nationally network, democratizing process which does not regard legal norms and people's morality.